2014
DOI: 10.1017/s0954579414000054
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibited social engagement in postinstitutionalized children: Differentiating normal from atypical behavior

Abstract: The most commonly reported socially aberrant behavior in postinstitutionalized (PI) children is disinhibited social engagement (DSE; also known as indiscriminate friendliness). There is no gold standard for measurement of this phenomenon or agreement on how to differentiate it from normative behavior. We adopted a developmental psychopathology approach (Cicchetti, 1984) to study this phenomenon by comparing it to normative social development and by studying its patterns over time in 50 newly adopted PI childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
2
34
0
4
Order By: Relevance
“…A recent study suggested that physical touching of unfamiliar adults during a laboratory paradigm in which the stranger makes overtures to the child may distinguish indiscriminate behavior from ordinary sociability more readily than verbal interaction (Lawler et al, 2014). In keeping with the link between social neglect and indiscriminate behavior, evidence is consistent that indiscriminate behavior is readily apparent in a minority of young children being raised in institutions Zeanah et al, 2005), adopted from institutions (Chisholm, 1998;O'Connor et al, 2003), and in maltreated children in foster care Zeanah et al, 2004).…”
Section: Indiscriminate Behaviormentioning
confidence: 94%
“…A recent study suggested that physical touching of unfamiliar adults during a laboratory paradigm in which the stranger makes overtures to the child may distinguish indiscriminate behavior from ordinary sociability more readily than verbal interaction (Lawler et al, 2014). In keeping with the link between social neglect and indiscriminate behavior, evidence is consistent that indiscriminate behavior is readily apparent in a minority of young children being raised in institutions Zeanah et al, 2005), adopted from institutions (Chisholm, 1998;O'Connor et al, 2003), and in maltreated children in foster care Zeanah et al, 2004).…”
Section: Indiscriminate Behaviormentioning
confidence: 94%
“…Further, Rutter et al (2010) identified a group of 29 children who show continuously elevated signs of DSED from early childhood through 15 years of age. Lawler et al (in press) showed diminution in signs of physical (but not non-physical) social engagement with a stranger in young children adopted internationally from institutions and foster care over an 8-month beginning one to three months after adoption.…”
Section: Course and Outcomesmentioning
confidence: 99%
“…The rationale for defining the indiscriminate behavior phenotype as DSED in DSM-5 as opposed to disinhibited attachment disorder as in ICD-10, is that the data indicate that the core deficit of the disorder is not non-selective attachment behaviors, but more about unmodulated and indiscriminate social behavior, especially initial approaches to and interaction with unfamiliar adults. The justification for the change is supported by the assessment of indiscriminate behavior in numerous studies of institutionalized (Soares et al, 2014; Tizard & Rees, 1975; Zeanah et al, 2002, Zeanah et al, 2005) post-institutionalized (Bruce, Tarullo, & Gunnar, 2009; Smyke et al, 2010; Lawler et al, in press) and deprived children in foster care (Bruce, Tarullo & Gunnar, 2009; Oosterman & Schuengel, 2007; Pears et al, 2010; Zeanah et al, 2004). In these studies, what is disinhibited is children’s behavior with unfamiliar adults rather than with their putative attachment figures, for whom they may show focused attachment behaviors and preferential comfort seeking.…”
Section: Clinical Presentation: Classification and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite expectations that children adopted from institutions would display dysregulation in the form of marked increases in clinical levels of internalizing and externalizing problems, this has not been readily observed in childhood (Gunnar & van Dulmen, 2007; Juffer & Van Ijzendoorn, 2005), although it may emerge in adolescence (Kreppner et al, 2010). Unlike internalizing and externalizing disorders, dysregulation in the form of symptoms of disinhibited social engagement disorder (DSED; Lawler, Hostinar, Mliner, & Gunnar, 2014; Zeanah & Smyke, 2015) and attention-deficit/hyperactivity disorder (ADHD) are readily observed during childhood in post-institutionalized (PI) children (Pollak et al, 2010; Roy, Rutter, & Pickles, 2004; Rutter et al, 2001). These problems are so prevalent among PI children that some have suggested these excessive approach symptoms and lack of inhibition represent a core feature of institutional deprivation (Kreppner, O’Connor, & Rutter, 2001; Kumsta et al, 2010).…”
mentioning
confidence: 99%